Harmony with Nature: A Literature Review of Islamic and Perennial Values in Cikondang Indigenous Traditions - Supandi, Didi; Sa'ari, Che Zarrina binti; Abdillah, Abdillah; Naan, Naan (UIN Maulana Malik Ibrahim Malang, 2024)
The Cikondang indigenous community, one of the indigenous communities in Bandung Regency, holds a wealth of rich and diverse cultural values, including Islamic and timeless values that serve as guidelines for life. However, in an era of modernization and rapid environmental change, challenges to the preservation of such traditions and values are increasing. A lack of understanding and documentation regarding the relationship between these values and harmony with nature can result in the loss of cultural identity and damage the balance of local ecosystems. Therefore, this research aims to explore and analyze existing literature to understand how Islamic and perennial values are reflected in the traditions of the Cikondang community and how these values can contribute to efforts to maintain harmony between humans and nature. The research method used is a literature review. The selected literature includes journal articles, books, and academic sources relevant to the themes of local wisdom, religious values, and community relations with the environment, with a focus on publications from the last two decades. The results demonstrate that there is an integration of Islamic and perennial values in the Cikondang indigenous community. These values create a social system that encourages collaboration between humans and nature, where the Cikondang people see themselves as part of the ecosystem, not its master. Islamic values address environmental management, such as the concept of khalifah (stewardship), encouraging people to preserve natural resources. Similarly, perennial values promote respect for nature and encourage strengthening the relationship between humans and nature. Masyarakat adat Cikondang, salah satu komunitas adat di Kabupaten Bandung, memiliki kekayaan nilai budaya yang kaya dan beragam, termasuk nilai-nilai Islam dan nilai-nilai abadi yang menjadi pedoman hidup. Namun, di era modernisasi dan perubahan lingkungan yang cepat, tantangan terhadap pelestarian tradisi dan nilai-nilai tersebut semakin meningkat. Kurangnya pemahaman dan dokumentasi mengenai hubungan antara nilai-nilai ini dengan keharmonisan alam dapat menyebabkan hilangnya identitas budaya serta merusak keseimbangan ekosistem lokal. Oleh karena itu, penelitian ini bertujuan untuk mengeksplorasi dan menganalisis literatur yang ada guna memahami bagaimana nilai-nilai Islam dan abadi tercermin dalam tradisi komunitas Cikondang dan bagaimana nilai-nilai ini dapat berkontribusi pada upaya menjaga keharmonisan antara manusia dan alam. Metode penelitian yang digunakan adalah tinjauan literatur. Literatur yang dipilih mencakup artikel jurnal, buku, dan sumber akademis yang relevan dengan tema kearifan lokal, nilai-nilai keagamaan, dan hubungan masyarakat dengan lingkungan, dengan fokus pada publikasi dua dekade terakhir. Hasil penelitian menunjukkan adanya integrasi nilai-nilai Islam dan abadi dalam komunitas adat Cikondang. Nilai-nilai ini menciptakan sistem sosial yang mendorong kolaborasi antara manusia dan alam, di mana masyarakat Cikondang melihat diri mereka sebagai bagian dari ekosistem, bukan penguasanya. Nilai-nilai Islam berbicara tentang pengelolaan lingkungan, seperti konsep khalifah (pemimpin) di bumi, yang mendorong orang untuk melestarikan sumber daya alam. Demikian pula, nilai-nilai abadi menghormati alam dan mendorong pemeliharaan serta penguatan hubungan antara manusia dan alam.